RELATIONSHIP BETWEEN STRENGTH/POWER AND DYNAMIC BALANCE IN 1ST-YEAR UNDERGRADUATE STUDENTS – PILOT STUDY - NEGRU, Ioan Niculaie (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2023)
Aim: Examine the relationship between lower limb strength/power and dynamic balance, and whether lower limb strength differences influence balance. Methods: 85 subjects (mean age 20.14, ±0.44) - female (n=63) and male (n=22) 1st-year undergraduate students - participated in this study. Standing long jump and single leg triple hop jump tests were used to determine strength/power, and balance board was used to determine balance. Results: The statistical analysis has revealed no statistically significant correlation between lower limb strength and the average time on balance board after three essays (r = 0.102, df = 83, p = 0.35). As for the relationship between the difference in the scores of the three successive single leg hop jumps and the average time on balance board after three essays, no statistically significant correlation has been found in this case either (r = 0.136, df = 83, p = 0.21). The average score of hop jumps on right leg is (M = 412.54 cm) and the average score of hop jumps on left leg is (M = 403.07 cm); according to the statistical analysis, they differ significantly (t = 2.227, df = 84, p = 0.029). There is a significant difference (t = - 2.625, df = 84, p = 0.01) between the average time on balance board after the first essay (M = 24. 77) and the average time on balance board after the third essay (M = 27.21). Conclusions: In this study, the statistical analysis has revealed no statistically significant correlation between lower limb strength/power and balance. No statistically significant correlation has been found between lower limb strength difference and balance either. Balance board is important in balance development, as shown by the average scores of the three essays (M1 = 24.77, M2 = 26.52, M3 = 27.21). Received 2023 May 11; Revised 2023 July 9; Accepted 2023 July 10; Available online 2023 July 30; Available print 2023 August 30.